Scientific approach in quranic exegesis : the emergence and issues / Ahmad Thaqif Ismail and Aqdi Rofiq Asnawi - Ismail, Ahmad Thaqif; Asnawi, Aqdi Rofiq (Universiti Teknologi MARA, 2021)
This research studies the concept of scientific exegesis (Al-Tafsīr Al-ʿIlmī)which recently gained considerable significance in the Muslim world in order to understand the Quran in this contemporary era. In the beginning, we define the scientific exegesis, shedding light on its history in terms of its emergence, time context, scholars and their arguments. Later, we identify and discuss the following theoretical and practical issues of the scientific exegesis. It applies two methodologies, historical to collect relevant data and analysis to scrutinize the collected data. The study concludes that there have been numerous tafsīr that use scientific exegesis approaches that contain significant methodological issues which need to be examined to shed better light on this problem. On the basis of making the Quran to be contemporarily understood, this study suggested that the integration of both sciences and revealed knowledge should be applied in a correct methodological way or it will lead to serious misunderstanding of the Quran.